Current Evidence for the Use of Smoflipid® Emulsion in Critical Care Patients for Parenteral Nutrition. (21st November 2018) - Leguina-Ruzzi, Alberto A.; Ortiz, Rina
Abstract : There are strong data showing that malnutrition is highly prevalent in intensive care unit patients (20–50% in the worldwide), presenting a negative accumulated body energy balance. This results in an increased mortality, infections, and hospital length stay with high costs associated with the total treatment. Parenteral nutrition is the first option when the patient's physical condition is not suitable for oral nutrient intake. It is composed essentially by lipids as an energy source, metabolic, and structural function. However, these patients also require a mixture of essential and nonessential fatty acids (SMOF emulsions) to supply not only energy needs but also restore immunological, anti-inflammatory, and proregenerative functions. A revision of the safety and efficacy of Smoflipid® in patients requiring long-term parenteral nutrition was discussed here. Although controversial data are available indicating the contraindications or effectiveness of its use, most of studies presented indicate favorable benefits associated with improved clinical outcomes. The reported roles of this supplementation include positive immunomodulatory and anti-inflammatory effects, positive impact in liver function, reduction of hospital stay, and nosocomial infections as additional contributions to its energetic role, which in many cases results in reduced total costs per patient. Finally, many authors propose that the use of Smoflipid® should become a gold standard of parenteral nutrition in intensive unit care patients and that the costs associated with this supplement should not be limiting for its use, not only to improve the clinical outcome but also to reduce the treatment costs.